ANALYSIS OF METHODS AND TECHNIQUES IN CONTEMPORARY ELECTORAL GEOGRAPHY RESEARCH IN BRAZIL - Guimarães, Glauber Cardoso; Cigolini, Adilar Antonio (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
This article aims to classify the methodological procedures used by academic works in the field of Electoral Geography. The studies were classified according to 4 typologies: (i) descriptive and statistical cartographic representation; (ii) spatial quantitative methods; (iii) individual voter behavior and (iv) social logic of electoral behavior. The following categories were added: (v) state of the art / knowledge and (vi) others. To carry out the survey, research was carried out: in the catalog of CAPES theses and dissertations with the term electoral geography and added the filters: temporal from 2016 and areas of knowledge Political Science and Geography; in 63 websites of journals on Geography; on Scielo platform and on Google Scholar platform. The survey resulted in 45 academic papers. It was evident that the distribution of studies is egalitarian between Political Science and Geography. There is a predominance of quantitative methods, especially evaluating the scope of Political Science, while in Geography there is a similar distribution of typologies. We conclude that the diversity of methods is natural in a science with more than a century of history and we suggest research in conference proceedings and research groups for future surveys.